An interdisciplinary approach to teaching professionally-oriented english (Eurasian Journal of Philology Science and Education, 2016)
The paper considers application of interdisciplinary approach to teaching professionally-oriented English for the students of physics. Interdisciplinary pedagogical practice allows the teacher to cross the traditionalboundaries of disciplinecentered teaching by drawing knowledge from two or more academic disciplines. In teaching foreign languages at non linguistic faculties it is especially important to develop skills of rendering of special scientific texts. This work fully implements possibilities of interdisciplinary approach to teaching foreign languages. Therefore, one of the tasks of teaching English at the natural science faculties is to formskills of working with the original Englishlanguage literature on specialty, and in particular, to develop skills of writing summaries of the texts. Students have to learn how to write annotations and abstract in the English language to the scientific articles written in their native language. On the example of teaching English at the of Physics & Technology it is shown that interdisciplinary approach to helps students to gain better understanding of physical laws.
Keywords: interdisciplinary approach; professionallyoriented English language; writing summary